Pathogenicities and GP43kDa gene of three Paracoccidioides brasiliensis isolates originated from a nine-banded armadillo (Dasypus novemcinctus) - Sano, A.; Defaveri, J.; Tanaka, R.; Yokoyama, K.; Kurita, N.; Franco, M.; Coelho, KIR; Bagagli, E.; Montenegro, M. R.; Miyaji, M.; Nishimura, K. (Kluwer Academic Publ, 1998)
We studied three different isolates of Paracoccidioides brasiliensis obtained from the mesenteric lymph node (D3LY1), the spleen (D3S1) and the liver (D3LIV1) of the same armadillo (Dasypus novemcinctus ).Pulmonal inflammatory area was evaluated by intravenous inoculation of 10(6) yeast cells of each isolates in young, male, ddY mice. Moreover, the partial sequence of GP43kDa gene of P. brasiliensis was analyzed. The lung inflammatory area was greater in animals inoculated with isolate D3S1. The partial sequence of GP43kDa gene indicated that isolate D3S1 is different from isolates D3LY1 and D3LIV1. This study suggested that the same armadillo might be susceptible to multiple P. brasiliensis isolates simultaneously.
Keywords: armadillo; GP43kDa gene; Paracoccidioides brasiliensis; pathogenicity